The effect of antipsychotic-induced extrapyramidal disorders on patient’s compliance with schizophrenia (a clinical case) - E. G. Rahim; E. G. Kornetova; A. A. Goncharova; A. N. Кornetov; A. V. Semke (Бюллетень сибирской медицины)
Extrapyramidal disorders are common adverse events in antipsychotic therapy. However, their diagnosis is difficult due to broad differential diagnosis, and often their specific clinical variant is not recognized, and timely intervention is not performed, which leads to severe patient suffering. This affects the quality of life of patients with schizophrenia and leads to their refusal to receive therapy, which aggravates the course of the disease. The article presents a clinical case of a 33-year-old patient at a psychiatric hospital with schizophrenia combined with such rare severe extrapyramidal disorders as antipsychotic-induced tardive dyskinesia and tardive dystonia.The diagnosis was carried out in accordance with the criteria of the International Classification of Diseases, Tenth Revision (ICD-10). The intensity of clinical manifestations was assessed using the Positive and Negative Syndrome Scale (PANSS), the Abnormal Involuntary Movement Scale (AIMS), and the Barnes Akathisia Rating Scale (BARS). Compliance was assessed using the Method for Measuring Medication Adherence in Psychiatry. Detailed differential diagnosis of tardive dyskinesia and tardive dystonia with akathisia and Huntington’s disease was presented. Substantiated treatment strategy and positive clinical dynamics with increased compliance were described.